Projection of Future Global Offshore Wind Energy Resources using CMIP Data. Issue 2 (15th March 2019) - Zheng, Chong-wei; Li, Xue-yan; Luo, Xia; Chen, Xuan; Qian, Yu-hao; Zhang, Zhen-hua; Gao, Zhan-sheng; Du, Zhi-bo; Gao, Yuan-bo; Chen, Yun-ge
Abstract: Offshore wind energy has the potential to ease energy and environmental crises, improve people's living standards on remote islands, and, finally, make contributions to sustainable development. Accurate energy evaluations should be performed before the exploitation of offshore wind energy; this includes not only assessments of the resource's historical characteristics but also a focused effort on understanding future issues. Using simulated wind data from the Coupled Model Intercomparison Project, phase 5 (CMIP5), this paper compares and analyses wind energy characteristics globally for the 2080–2099 period (future) relative to the 1980–1999 period (past). The classification of both past and future wind energy is also presented. The results show a positive trend for future global offshore wind energy. Compared with the past, the extent of areas with wind power density (WPD) greater than 400 W m −2 will expand. In the future, across most of the global oceans, the effective wind speed occurrence and the occurrence of a WPD higher than 200 W m −2 will be greater than that in the past, generally by 10%. The extents of the sub-rich, available, and poor regions will decrease, while the regions with a wind energy class of 7 will expand. The future wind energies of the North and South Poles show a "seesaw" phenomenon.